New AIM/CIPS global observations of gravity waves near 50–55 km. Issue 13 (7th July 2017) - Randall, C. E.; Carstens, J.; France, J. A.; Harvey, V. L.; Hoffmann, L.; Bailey, S. M.; Alexander, M. J.; Lumpe, J. D.; Yue, J.; Thurairajah, B.; Siskind, D. E.; Zhao, Y.; et al.
Abstract: This paper describes a new data set from the Aeronomy of Ice in the Mesosphere (AIM) Cloud Imaging and Particle Size (CIPS) instrument, from which gravity waves (GWs) at an altitude of 50–55 km can be inferred. CIPS is sensitive to GWs with horizontal wavelengths from ~15 to 600 km and vertical wavelengths longer than 15 km. Several examples of GWs in CIPS observations are shown, including waves associated with the Andes Mountains, island topography, convection, the polar night jet, and the tropospheric jet stream. GW signatures in the CIPS data are shown to agree well with near‐coincident but lower altitude measurements from the Atmospheric Infrared Sounder (AIRS) in June of 2016. Results suggest the power of combining CIPS measurements with those from other instruments to investigate GW filtering and propagation. The CIPS data set opens new areas of inquiry, enabling comprehensive investigations of GWs in the middle atmosphere on a near‐global scale. Key Points: New gravity wave data set from the Aeronomy of Ice in the Mesosphere Cloud Imaging and Particle Size satellite instrument Near‐global coverage at 50–55 km altitude for waves with horizontal wavelength from 15 to 600 km and vertical wavelength longer than 15 km New data fill key spatial and temporal gaps in current record and are particularly relevant to vertical propagation of gravity waves Plain Language Summary: This paper describes a new data set from the Cloud Imaging and Particle Size instrument on the NASA Aeronomy of Ice in the Mesosphere satellite. The data set can be used to infer atmospheric gravity waves at an altitude of 50‐55 km. Several examples of gravity waves are shown, including waves associated with the Andes Mountains, island topography, convection, the polar night jet, and the tropospheric jet stream. Gravity wave signatures in the new data set are shown to agree well with near‐coincident but lower altitude measurements from the satellite‐based Atmospheric Infrared Sounder. Results suggest the power of combining the new data with measurements from other instruments to investigate gravity wave filtering and vertical propagation. This data set opens new areas of inquiry, enabling comprehensive investigations of gravity waves in the middle atmosphere on a near‐global scale. Such studies are important because gravity waves drive the circulation in the middle and upper atmosphere, thereby impacting global atmospheric structure, composition, and variability.